Scintillation light increase of carbontetrafluoride gas at low temperature. (21st December 2021) - Mizukoshi, K.; Maeda, T.; Nakano, Y.; Higashino, S.; Miuchi, K.
Abstract: Scintillation detector is widely used for the particle detection in the field of particle physics. Particle detectors containing fluorine-19 ( 1 9F) are known to have advantages for Weakly Interacting Massive Particles (WIMPs) dark matter search, especially for spin-dependent interactions with WIMPs due to its spin structure. In this study, the scintillation properties of carbontetrafluoride (CF4 ) gas at low temperature were evaluated because its temperature dependence of light yield has not been measured. We evaluated the light yield by cooling the gas from room temperature (300 K) to 263 K. As a result, the light yield of CF4 was found to increase by (41.0 ± 4.0stat. ± 6.6syst. )% and the energy resolution was also found to improve at low temperature.